PS-BPC07-4: RENOPROTECTIVE EFFECTS OF SGLT2 INHIBITORS AND RELATED FACTORS IN CHRONIC HEART FAILURE PATIENTS WITH DIABETES. (January 2023) - Horio, Takeshi; Yokouchi, Go; Matsumoto, Naoki; Fukuda, Kohei; Yoshimura, Ryutaro; Fujiwara, Ryosuke; Matsuoka, Yujiro; Sakamoto, Yuya; Fujimoto, Kohei; Kasayuki, Noriaki
Abstract : Objective: Large-scale clinical trials have shown that sodium-glucose cotransporter 2 (SGLT2) inhibitors have beneficial effects on not only cardiovascular and renal outcomes but also the preservation of renal function in patients with diabetes mellitus and/or chronic kidney disease. However, the effect of SGLT2 inhibitors on renal function in heart failure remains to be fully elucidated. The present study investigated whether SGLT2 inhibitors exert renoprotective effects in chronic heart failure patients with diabetes, by comparing serial changes in estimated glomerular filtration rate (eGFR) for years before and after SGLT2 inhibitor administration. In addition, if SGLT2 inhibitors had a favorable effect on renal function, we examined what cardiac/hemodynamic and noncardiac factors were involved in its effect. Design and method: Methods: From 83 outpatients with chronic heart failure and type-2 diabetes mellitus taking both SGLT2 inhibitors and loop diuretics, 50 patients whose eGFR levels were continuously measured for more than 6 months both before and after administration of SGLT2 inhibitors were selected. In this longitudinal observational study, eligible patients were retrospectively followed up before and after SGLT2 inhibitor administration. Clinical data such as body weight, blood pressure, heart rate, blood (hematological and biochemical) parameters, echocardiographic parameters, and medical treatment were collected at respective ends of the follow-up periods before and after SGLT2 inhibitor administration. All eGFR values were separately plotted before and after the initiation of treatment with SGLT2 inhibitors along the time course axis and the slope of the linear regression curve was calculated as an annual change in eGFR. Results: The mean follow-up periods before and after SGLT2 inhibitor administration were 2.6 and 1.9 years, respectively. Changing rates of eGFR per year were significantly improved after treatment with SGLT2 inhibitors (mean ± SD, -5.78 ± 7.67 to -0.43 ± 10.81 mL/min/1.73m 2 /year, p = 0.006). The daily doses of loop diuretics were not altered after SGLT2 inhibitor administration. Body weight decreased and hematocrit and hemoglobin increased by SGLT2 inhibitor administration, but neither change was not associated with the change in eGFR slope before and after SGLT2 inhibitor administration. While, the decrease in inferior vena cava diameter was significantly correlated with the improvement of eGFR decline slope after SGLT2 inhibitor administration (r = -0.428, p = 0.004). Conclusions: This study demonstrated that long-term treatment with SGLT2 inhibitors ameliorated annual decline in eGFR in Japanese patients with chronic heart failure. The observed renoprotective effect may have been mediated by improved venous congestion.